Traumatic fracture-dislocation of the hip following rugby tackle: a case report - Venkatachalam, S.; Heidari, N.; Greer, T. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2009)
Posterior fracture-dislocation of hip is uncommonly encountered in rugby injuries. We report such a case in an adult while playing rugby. The treating orthopaedician can be caught unaware and injuries in such sports can be potentially misdiagnosed as hip sprains. Immediate reduction of the dislocation was performed in theatres. The fracture was fixed with two lag screws and a neutralization plate. This led to early rehabilitation and speedy recovery with return to sporting activities by 12 months.